2020
DOI: 10.3389/fmolb.2019.00153
|View full text |Cite
|
Sign up to set email alerts
|

“An End to a Means”: How DNA-End Structure Shapes the Double-Strand Break Repair Process

Abstract: Endogenously-arising DNA double-strand breaks (DSBs) rarely harbor canonical 5 ′ -phosphate, 3 ′ -hydroxyl moieties at the ends, which are, regardless of the pathway used, ultimately required for their repair. Cells are therefore endowed with a wide variety of enzymes that can deal with these chemical and structural variations and guarantee the formation of ligatable termini. An important distinction is whether the ends are directly "unblocked" by specific enzymatic activities without affecting the integrity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 108 publications
(140 reference statements)
0
5
0
Order By: Relevance
“…These two models of how persistent R loops impact CSR are not mutually exclusive, as DSB end structure directly affects repair protein binding affinity and which proteins are necessary for successful repair ( Chang et al, 2017 ; Serrano-Benítez et al, 2019 ; Symington, 2016 ). We propose that persistent R loops promote the formation of long (>6 bp) ssDNA tails, increasing the frequency of error-prone EJ at switch joins in Setx -/- , Rnaseh2b f/f , and Setx -/- Rnaseh2b f/f cells.…”
Section: Discussionmentioning
confidence: 99%
“…These two models of how persistent R loops impact CSR are not mutually exclusive, as DSB end structure directly affects repair protein binding affinity and which proteins are necessary for successful repair ( Chang et al, 2017 ; Serrano-Benítez et al, 2019 ; Symington, 2016 ). We propose that persistent R loops promote the formation of long (>6 bp) ssDNA tails, increasing the frequency of error-prone EJ at switch joins in Setx -/- , Rnaseh2b f/f , and Setx -/- Rnaseh2b f/f cells.…”
Section: Discussionmentioning
confidence: 99%
“…These two models of how persistent R loops impact CSR are not mutually exclusive, as DSB end structure directly affects repair protein binding affinity and which proteins are necessary for successful repair (H. H. Y. Chang et al, 2017; Serrano-Benitez, Cortes-Ledesma, & Ruiz, 2019; Symington, 2016). We propose that persistent R loops promote the formation of long (> 6 bp) ssDNA tails, increasing the frequency of error-prone EJ at switch joins in Setx -/- , Rnaseh2b f/f , and Setx -/- Rnaseh2b f/f cells.…”
Section: Discussionmentioning
confidence: 99%
“…Abundance and affinity would suggest that DNA-PK would likely be the first protein to arrive at a DSB, a point that has been debated, though recent evidence provides experimental evidence for the rapid association of DNA-PK with DNA ends in living cells (36). Biochemical and structural studies support the hypothesis that DNA-PK activation is driven by direct contact with DNA (37)(38)(39) and there is evidence that DNA structure and sequence play a unique and critical role in optimal DNA-PK activation (19;20). Previous work has shown that the Ku heterodimer is required for efficient NHEJ and functions as a scaffold for other NHEJ proteins to bind (40), including forming a critical interaction with DNA-PKcs.…”
Section: Discussionmentioning
confidence: 99%